VARIASI METODE MENGAJAR GURU DALAM MENGATASI KEJENUHAN SISWA DI SEKOLAH MENENGAH PERTAMA - Fatniaton Adawiyah (CV. Adiba Aisha Amira, 2025)
This study aims to determine how teachers vary their teaching methods to overcome student boredom in junior high schools. What are the obstacles in creating varied teaching methods for teachers to overcome student boredom in junior high schools? What efforts have been made to create varied teaching methods for teachers to overcome student boredom in junior high schools? This study uses a descriptive qualitative approach. To obtain data, the researcher used interviews, observation, and documentation. Data analysis in this study included data reduction, data presentation, and conclusion drawing. Data validity was checked using the researcher's diligence and data source triangulation. The stages of research in this study included the pre-field stage, the fieldwork stage, the data analysis stage, and the report writing stage. The results of this study concluded that: 1) Islamic Education teachers at the school used the lecture method interspersed with the question and answer method. In addition to these methods, teachers sometimes also used the discussion method. 2) Obstacles include teachers' lack of ability to develop and apply varied learning methods, teachers' lack of knowledge about their students, such as their intelligence levels, talents, and interests; teachers' lack of maturity in preparing their teaching materials, which hinders the implementation of learning; and the lack of available facilities to support learning. 3) Efforts made by teachers to combine several learning methods, for example, a combination of lecture-question and answer and assignment methods, lecture-discussion and assignment methods, lecture-demonstration and experiment methods, and so on, as well as improving teaching skills, especially the skills of using varied methods in good and focused learning.